Classical trajectory simulations of photodissociation of CH3Br at surfaces - Ibrahim Ali , Noorbatcha (American Institute of Physics (AIP), 1992)
We have simulated the photodissociation of CH3Br adsorbed at a variety of surfaces. We have considered photodissociation at a smooth LiF (001) substrate and at three rough LiF surfaces which were constructed by removing atoms from the smooth surface. We have also considered photodissociation from several surfaces which have the same structure as the β phase of solid CH3Br to simulate dissociation from high coverages of the adsorbate where CH3Br ice is formed. The simulations were performed using the stochastic classical trajectory method. The asymptotic photofragment kinetic energy and angular distributions were determined and compared with the experimental results of Harrison e t a l. [J. Chem Phys. 8 9, 1475 (1988)] and Tabares e t a l. [J. Chem. Phys. 8 6, 738 (1987)]. When CH3Br is oriented with CH3 toward a surface, the CH3 kinetic energy distributions are shifted to much lower energies due to energy loss from multiple collisions with Br and the surface; the angular distributions are also significantly broadened. Much of the energy loss in these collisions goes into the translational mode of the Br fragments, causing the Br kinetic energy distributions to have a high‐energy tail. When the molecule is in this orientation in a restricted geometry, collisions from the CH3 fragment lead to more effective energy transfer causing the peak of the Br kinetic energy distributions to be shifted to much higher energies and the corresponding angular distributions to become narrower. The main features of the experimental results from photodissociation of CH3Br adsorbed on LiF can be qualitatively explained using the results of the classical trajectory simulations.